The Constitutionality of Outsourcing Job Regulation in the Law on Job Creation - Sisinaru, Sostones Y; Harijanti, Susi Dwi (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2022)
Government policy to adopt the idea of “omnibus law” through the forming of Job Creation Law aims to simplify investment and to fix regulations in Indonesia. Job creation Law consists of 11 clusters. One of the clusters regulates manpower mainly concerning Outsourcing Minimum Wage and termination of employment. This policy has potential to bring disadvantages to the interest of the workers and leads to protest by workers/labors. This study aims to investigate political direction of job Creation Law and question the constitutionality of the regulations of outsourcing work in Job Creation Law. Research method of this study was normative, meaning that by using legislation and conceptual approach to perform qualitative analysis. The result and Discussion of this study concludes that political direction of Job creation Law is still authoritarian politics so that resulting in Law that is conservative because the discussion about the Law did not involve the people participation. Moreover, the material formulation of outsourcing in Job Creation Bill has not aligned with the mandate of Supreme Court decision No 27/PUU-IX/2011.